Maternal Mortality-reduction Programme in Andhra Pradesh - Prakasamma, M (Journal of Health, Population and Nutrition, 2009)
Andhra Pradesh, a large state in southern India, has a high maternal mortality ratio of 195 per 100,000 livebirths despite the improvements in social, demographic and health indicators over the last two decades. This contrary situation has been analyzed using findings of different studies on maternal mortality, and four factors have been presented for consistently-high maternal mortality in the state. First, the disproportionately-high focus on family planning towards population stabilization reduced the emphasis on maternal health in the peripheral hospitals, resulting in low use of these facilities for childbirths. Second, the growth of services in Primary Health Centres was not given adequate emphasis, resulting in the weakening of the peripheral health system. Third, there was little emphasis on developing a cadre of midwives who would have primarily focused on maternal health. Lastly, the low status of women in the state has hampered timely referral and access to services. Key words: Health facilities; Maternal health; Maternal mortality; Safe motherhood; India doi: 10.3329/jhpn.v27i2.3365 J Health Popul Nutr 2009 April;27(2):220-234